Current Highlights About the Safety of Inorganic Nanomaterials in Healthcare - Perioli, Luana; Pagano, Cinzia; Ceccarini, Maria R. (Current Medicinal Chemistry, 2019)
In recent years inorganic materials are largely present in products intended for health care. Literature gives many examples of inorganic materials used in many healthcare products, mainly in pharmaceutical field. Silver, zinc oxide, titanium oxide, iron oxide, gold, mesoporous silica, hydrotalcite-like compound and nanoclays are the most common inorganic materials used in nanosized form for different applications in the health field. Generally, these materials are employed to realize formulations for systemic use, often with the aim to perform a specific targeting to the pathological site. The nanometric dimensions are often preferred to obtain the cellular internalization when the target is localized in the intracellular space. Some materials are frequently used in topical formulations as rheological agents, adsorbents, mattifying agents, physical sunscreen (e.g. zinc oxide, titanium dioxide), and others. Recent studies highlighted that the use of nanosized inorganic materials can represent a risk for health. The very small dimension (nanometric) until a few years ago represented a fundamental requirement; however, it is currently held responsible for the inorganic material toxicity. This aspect is very important to be considered as actually numerous inorganic materials can be found in many products available in the market, often dedicated to infants and children. These materials are used without taking into account their dimensional properties with increased risk for the user/patient. This review deals with a deep analysis of current researches documenting the toxicity of nanometric inorganic materials especially those largely used in products available in the market.
Keywords: dermatological products